2021
DOI: 10.1038/s41598-021-86721-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary supplementation with Nigella sativa (black seeds) mediates immunological function in male Wistar rats

Abstract: This experiment aimed to investigate the effect of dietary Nigella sativa on the cell-mediated immune response. Eighteen male Wistar rats were divided equally into a control group and treated groups that received black seeds at rates of 30 and 50 g/kg in the diet (Sa30 and Sa50 groups, respectively, for 30 days. The weight gain, feed intake, feed conversion ratio (FCR), and cell-mediated immune response were monitored after the injection of 0.1 mL of 10% phytohemagglutinin (PHA). The intumesce index, serum tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…In a comparable study, feeding of rabbits on diets containing black cumin seed greatly modulated their immune responses [ 59 ]. Similarly, dietary supplementation with N. sativa in male Wistar rats mediated immunological function [ 60 ]. These observations might explain the anti-inflammatory activity of black cumin [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparable study, feeding of rabbits on diets containing black cumin seed greatly modulated their immune responses [ 59 ]. Similarly, dietary supplementation with N. sativa in male Wistar rats mediated immunological function [ 60 ]. These observations might explain the anti-inflammatory activity of black cumin [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by Mahmoud et al, 2021 [ 29 ] demonstrated a high antiradical scavenging activity of NS seeds which was attributed to the high content of phenolic and flavonoid compounds. A study by Bocsan et al, 2021 [ 30 ], indicated that the NS oil has a high antiradical scavenging activity when tested against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical.…”
Section: Pharmacological Properties Of Nigella Sativamentioning
confidence: 99%
“…The supplementation of rats with NS seeds was able to cause an increase in catalase (CAT) activity and the total antioxidant activity in comparison with the control [ 29 ] ( Figure 6 ). In a clinical study, the antioxidant activity tested in vivo on healthy subjects by a daily administration of the aqueous extract (200–250 mL) during five days indicated a non-significant decrease on the sixth day of the MDA, and a non-significant increase of superoxide dismutase (SOD), while a significant increase of the erythrocyte glutathione GSH was noticed [ 31 ] ( Table 1 ).…”
Section: Pharmacological Properties Of Nigella Sativamentioning
confidence: 99%
“…Leaves are 2-3 in number, linear, pinnatisect (2.5-5 cm) and has tapering root; the flowers are white, yellow, pale blue color, with 5-10 petals on single long peduncle; sepals are acute, ovate, and clawed. A fruit capsule composed of united follicles (3)(4)(5)(6)(7), each including black seeds (0.2 cm x 0.1 cm) which are dicotyledonous, angular, trigonous, rigose, flattened, oblong, funnel shaped, tubercular having rough testa of white kernel; Seeds produce lemon like slightly aromatic odor when crushed and bitter in taste. The seed coat is rough, thin measuring about 0.3 mm thick.…”
Section: Plant Descriptionmentioning
confidence: 99%